SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 70% BIJI KALANGKALA (Litsea angulata Bl.) TERHADAP BAKTERI PENYEBAB JERAWATPropionibacterium acnes - Hafiz Ramadhan; Muhammad Arsyad; Putri Indah Sayakti (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2020)
Acne vulgaris or acne is a chronic inflammatory disease in the polysebaseus unit thatoften occurs especially in teenagers and adults, one of which is caused by thebacterium Propionibacterium acnes. Natural material that has the potential as anantibacterial is Kalangkala (Litsea angulata Bl.), where some people in SouthKalimantan use the seeds to treat boils. This research purposes to determine thecontent of secondary metabolites of 70% ethanol extract of Kalangkala seedsandtheir activities as antibacterial againts P.acnes. The phytochemical screening testincludes flavonoids, alkaloids, saponins, steroids-terpenoids and tannins. The methodof testing the antibacterial activity with the well diffusion method using extractconcentration 100%; 50%; 25%; 12.5%; 6.25%; and 3.125%. The results showed70% ethanol extract of Kalangkala seeds containing flavonoids, alkaloids, saponinsand tannins. The antibacterial activity of 70% ethanol extract of Kalangkala seedsagaints Propionibacterium acnes bacteria with well diffusion method was obtainedby MIC that is 25% with an average inhibition zone diameter of 8,667 mm whichincluded the moderate category as an antibacterial agent.